Effects of Laser Irradiation on Caries Prevention - Rezaei, Yashar; Bagheri, Hossein; Esmaeilzadeh, Maryam (Journal of Lasers in Medical Sciences, 2012)
INTRODUCTION: Although dental caries is a preventable disease, it is still common and remains a public health problem. One of the potentially effective preventive measures is the use of lasers. The purpose of this study was to review the studies about use of laser irradiation on the inhibition of carious lesions and the effectiveness of different commercial laser type (Nd:YAG, CO2, and Argon). METHODS: A literature search included journal databases, existing systematic reviews, and studies identified by content experts. Studies meeting inclusion criteria were assessed for quality. RESULTS: Some studies have demonstrated the potential preventive effect of laser irradiation on sound enamel; the effect of irradiation on white spot lesions is still unclear. The effects of irradiating demineralized enamel surfaces coupled with the use of topical fluoride application is also still unclear and further research needs to be conducted in this area. Laser irradiation alone can significantly enhance acid resistance of sound enamel surfaces and prevent caries progression. CONCLUSION: Combined use of topical fluoride application and laser irradiation on sound enamel surfaces has provided the best protection against caries initiation and progression. Laser irradiation was of limited value in managing incipient carious lesions. Argon laser use may be easier clinically due to its large and visible beam diameter, which allows for irradiation of the whole surface of the tooth instead of the overlapping and time consuming pattern of the CO2 laser.